(untitled) (Research, Society and Development, 2024)
Objective: To evaluate user satisfaction with the Telemedicine and Telehealth Platform. Methods: This is a cross-sectional, observational, quantitative, and analytical study using an instrument that seeks to measure patient satisfaction with a telehealth service in a virtual environment. A self-filling form created using the Google Forms tool was used, anonymously and voluntarily, the link to which was sent via the WhatsApp Business application, following all teleservices carried out. The questionnaire was previously validated by the team from the E-Health Unit of the Hospital das Clínicas of the Federal University of Pernambuco. Results: Of the 367 respondents, 304 (82.8%) rated the technical support as excellent, 340 (92.6%) rated the health professional as excellent, 316 (86.1%) had their needs met and 342 (93.2%) would use the service again. The most common difficulties were accessing the link 63 (17.2%), activating the camera and/or microphone 48 (13.1%), unstable connection 31 (8.4%). Conclusion: It is concluded that telehealth brings excellent benefits for patient care in various health specialties, a fact confirmed via numerical results and patient reports, where we obtained a high acceptance of the modality.